New Data On Pellaea Stictica Dallas (Heteroptera: Pentatomidae) In South America - Carvajal Morales, Mariom Adriana; Vargas, Catalina; Faundez Peña, Eduardo Ivan (My University, 2019)
New records are given for the pentatomid Pellaea stictica Dallas, 1851. The new records extend the distribution of the species in Perú towards the south. The presence of the species in Chile is confirmed by the collection of new material. The first exact locality record from Paraguay is provided. Additionally, the first teratological case in this species is described. The case belongs to a right antennal oligomery with atrophy and anarthrogenesis.
Nuevos datos sobre Pellaea stictica Dallas (Heteroptera: Pentatomidae) en Sudamérica
Keywords: New Records; Pentatominae; Chile; Paraguay; Perú; Teratology